2017
DOI: 10.1155/2017/5189138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Four Oxidative Stress‐Responsive MicroRNAs, miR‐34a‐5p, miR‐1915‐3p, miR‐638, and miR‐150‐3p, in Hepatocellular Carcinoma

Abstract: Increasing evidence suggests that oxidative stress plays an essential role during carcinogenesis. However, the underlying mechanism between oxidative stress and carcinogenesis remains unknown. Recently, microRNAs (miRNAs) are revealed to be involved in oxidative stress response and carcinogenesis. This study aims to identify miRNAs in hepatocellular carcinoma (HCC) cells which might involve in oxidative stress response. An integrated analysis of miRNA expression signature was performed by employing robust rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 43 publications
3
46
0
1
Order By: Relevance
“…Growing evidence has confirmed that miRNAs can be considered as potential targets and modulators of oxidative-stress-related pathways [61]. By analysis of miRNA expression signature implicated in oxidative stress-related pathways, several miRNAs were identified and termed as oxidative stress-responsive miRNAs [62]. The increasing number of studies shows that intracellular ROS can either inhibit or induce miRNA expression level, which results in subsequent biological effects through regulation of their direct target genes ( Figure 2) [63].…”
Section: Oxidative Stress and Mirnamentioning
confidence: 99%
“…Growing evidence has confirmed that miRNAs can be considered as potential targets and modulators of oxidative-stress-related pathways [61]. By analysis of miRNA expression signature implicated in oxidative stress-related pathways, several miRNAs were identified and termed as oxidative stress-responsive miRNAs [62]. The increasing number of studies shows that intracellular ROS can either inhibit or induce miRNA expression level, which results in subsequent biological effects through regulation of their direct target genes ( Figure 2) [63].…”
Section: Oxidative Stress and Mirnamentioning
confidence: 99%
“…Accumulating evidence has reported differences in miRNAs expression profiles between normal and OA cartilage samples, demonstrating their role in the development and progression of OA [ 8 , 9 , 10 ]. Recently, some oxidative stress-responsive miRNAs were identified after the treatment of various cell types with H 2 O 2 [ 11 ]; otherwise, cellular mechanisms regulating oxidative stress were fine-tuned by particular miRNAs [ 12 ]. For these reasons, miRNAs seem to be implicated in the articular damage triggered by oxidative stress in OA pathology.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA Associations with "Oxidative Stress." On the other hand, if we look at nodes that are connected by a small number of articles such as the nodes for microRNAs in Figure 1, Step 3, we find "MIR23A" [129], "MIR34A" [130], "MIR155" [131], "MIR210" [132], and "MIR106B" [133] being associated in our KB with "oxidative stress" via "6," "4," "3," "2," and "1" articles, respectively.…”
Section: Example 1: Finding the Relevant Concepts Of Differentmentioning
confidence: 99%